Analisa Target Pajak Tak Tertagih Pada Pajak Bumi dan Bangunan Studi kasus pada Kabupaten Bengkalis - Husni Mubarak; Ari Ramdani (Politeknik Negeri Bengkalis, 2020)
This research title is Analysis of Target Value from Uncollected Tax on Land and Building Tax covers in the Bengkalis district. The data used is the Regional Revenue Agency (BAPENDA) for the past 3 years. The results of this study find that Uncollected taxes for world tax and tax (PBB tax) in Bengkalis region is very high, 52 percent or it same with Rp. 9,219,974,176 in total from PBB tax 2019. Have 6 sub-districts failure to collect PBB tax, they are have less value than 50% of 11 sub-districts, and only 1 sub-district have sucsess performs with a failure value only 5.84%, it mean the community's ability to pay PBB tax is over 96%.